Reverse Channel Design: The Case of Competing Retailers - Savaskan, R. Canan; Van Wassenhove, Luk N. (Management Science, 2006)
The economical and environmental benefits of product remanufacturing have been widely recognized in the literature and in practice. In this paper, we focus on the interaction between a manufacturer’s reverse channel choice to collect postconsumer goods and the strategic product pricing decisions in the forward channel when retailing is competitive. To this end, we model a direct product collection system, in which the manufacturer collects used products directly from the consumers (e.g., print and copy cartridges) and an indirect product collection system, in which the retailers act as product return points (e.g., single-use cameras, cellular phones). We first examine how the allocation of product collection to retailers impacts their strategic behavior in the product market, and we discuss the economic trade-offs the manufacturer faces while choosing an optimal reverse channel structure. When a direct collection system is used, channel profits are driven by the impact of scale of returns on collection effort, whereas in the indirect reverse channel, supply chain profits are driven by the competitive interaction between the retailers. Subsequently, we show that the buy-back payments transfered to the retailers for postconsumer goods provide a wholesale pricing flexibility that can be used to price discriminate between retailers of different profitability.